2018
DOI: 10.1111/ctr.13142
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of adherence and tolerability of prolonged‐release tacrolimus (Advagraf™) in kidney transplant patients in Germany: A multicenter, noninterventional study

Abstract: This study assessed adherence to prolonged-release tacrolimus (PR-T)-based immunosuppression during routine maintenance of renal transplant recipients in Germany.Patients had received PR-T for ≥1 month at inclusion. Data were collected during four visits (V): baseline (V1), 6 (V2), 12 (V3), and 18 (V4) months. Composite primary endpoint: nonadherence at V4, defined as self-reported nonadherence on the Basel in medication), and treatment-related factors (eg, adverse events and duration of treatment). 7 In parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 24 publications
2
27
0
Order By: Relevance
“…Self‐reported nonadherence using BAASIS © in this population was 29% at 1‐year, which is in line with previous studies . As other reports also have shown , the majority of these NoAd patients took all the prescribed doses but had a time deviation (22%). A 2‐h time deviation as the BAASIS © form defines as nonadherence may seem rigid and its clinical relevance in RTxR has been questioned .…”
Section: Discussionmentioning
confidence: 99%
“…Self‐reported nonadherence using BAASIS © in this population was 29% at 1‐year, which is in line with previous studies . As other reports also have shown , the majority of these NoAd patients took all the prescribed doses but had a time deviation (22%). A 2‐h time deviation as the BAASIS © form defines as nonadherence may seem rigid and its clinical relevance in RTxR has been questioned .…”
Section: Discussionmentioning
confidence: 99%
“…As many of the developed tools do not evaluate the timing perspectives, an important aspect of immunosuppressive adherence is missing. BAASIS ® has established predictive validities the recent years and is today the most frequently used adherence questionnaire in transplant recipients (194,(202)(203)(204)(205)(206). BAASIS ® follow the recent ABC taxonomy of medication adherence (160), and assess adherence using items of dose taking, timing, drug holidays, drug reduction and discontinuation.…”
Section: Patient Self-reportmentioning
confidence: 99%
“…Nevertheless, some new evidence suggests that moving from twice-daily to once-daily dosing of the mainstay of the immunosuppressive regimen, the calcineurin inhibitor, may ultimately shift non-adherence prevalence rates downward. Thus, following on a randomized clinical trial (RCT) demonstrating better adherence with once-daily tacrolimus dosing [9••], Lehner et al [10•] reported on a multisite longitudinal observational study of patients receiving once-daily dosing of tacrolimus. They found self-reported non-adherence rates of between 9 and 13% during the month before each study assessment time point (through a maximum of 18 months of follow-up).…”
Section: Prevalence Of Non-adherencementioning
confidence: 99%
“…In heavily studied components of the medical regimen (e.g., immunosuppression medication-taking), the added value of new studies documenting prevalence rates is likely to be small. Exceptions would be longitudinal observational studies, like the work of Lehner et al [10•], which focus on examining non-adherence rates among programs that adopted empirically supported adherence promotion strategies. However, for any new studies, it would be important to reconsider the cut points traditionally used to identify non-adherent patients.…”
Section: Prevalence Of Non-adherencementioning
confidence: 99%